Optimasi Proses Penyerapan CO2 dengan Adsorben Karbon Aktif Menggunakan Computational Fluid Dynamics (CFD) dan Response Surface Methodology (RSM) - Novi Sylvia; Lia Sobrina; Nasrun Nasrun (Jurnal Teknologi Kimia Unimal, 2020)
Biogas purification from carbon dioxide compounds due to can reduce the calorific value of methane (CH4). One application used in this case is adsorption using activated carbon. This study aims to simulate the absorption of CO2 using ANSYS R19.0 and to analyze percent adsorption, adsorption capacity and isothermal adsorption. Based on variations in bed height, flow rate and pressure, the highest percent percussion occurs at 10 cm bed height, 50 cm3/minute flow rate with a pressure of 1.4 atm and the lowest percent absorption occurs at 6 cm bed height, 150 cm3/minute flow rate with a pressure of 1.2 atm. Whereas the maximum absorption capacity occurs at 8 cm bed height, 50 cm3/minute flow rate at a pressure of 1.4 atm and minimum absorption capacity occurs at 8 cm bed height, flow rate of 150 cm3/minute at a pressure of 1 atm. This adsorption process occurs in the Langmuir isotherm with R2 approaching 1, which is equal to 0.9151. The optimization results were obtained at a flow rate of 50 cm3/minute, bed height 9.46 cm and 1.4 atm pressure.